Interaction of luteolin, naringenin, and their sulfate and glucuronide conjugates with human serum albumin, cytochrome P450 (CYP2C9, CYP2C19, and CYP3A4) enzymes and organic anion transporting polypeptide (OATP1B1 and OATP2B1) transporters - Kaci, Hana; Bodnárová, Slávka; Fliszár-Nyúl, Eszter; Lemli, Beáta; Pelantová, Helena; Valentová, Kateřina; Bakos, Éva; Özvegy-Laczka, Csilla; Poór, Miklós (Biomedicine & pharmacotherapy, 2023)
Luteolin and naringenin are flavonoids found in various foods/beverages and present in certain dietary supplements. After a high intake of these flavonoids, their sulfate and glucuronide conjugates reach micromolar concentrations in the bloodstream. Some pharmacokinetic interactions of luteolin and naringenin have been investigated in previous studies; however, only limited data are available in regard to their metabolites. In this study, we aimed to investigate the interactions of the sulfate and glucuronic acid conjugates of luteolin and naringenin with human serum albumin, cytochrome P450 (CYP2C9, 2C19, and 3A4) enzymes, and organic anion transporting polypeptide (OATP1B1 and OATP2B1) transporters. Our main findings are as follows: (1) Sulfate conjugates formed more stable complexes with albumin than the parent flavonoids. (2) Luteolin and naringenin conjugates showed no or only weak inhibitory action on the CYP enzymes examined. (3) Certain conjugates of luteolin and naringenin are potent inhibitors of OATP1B1 and/or OATP2B1 enzymes. (4) Conjugated metabolites of luteolin and naringenin may play an important role in the pharmacokinetic interactions of these flavonoids.
Keywords: flavonoidy; Luteolin; Flavonoids; Cytochrome P450 enzymes; Humans; Sulfates; glukuronidy; cytochrom P-450 CYP3A; Organic Anion Transporters; lidský sérový albumin; lidé; Human serum albumin; Glucuronides; Cytochrome P-450 CYP2C9; OATP transporters; cytochrom P450 CYP2C9; Cytochrome P-450 Enzyme System; Sulfate/glucuronide metabolites; přenašeče organických aniontů; Cytochrome P-450 CYP2C19; Naringenin; Serum Albumin, Human; Cytochrome P-450 CYP3A; luteolin; systém (enzymů) cytochromů P-450; cytochrom P450 CYP2C19; sírany